Digital Voice of Customer: Analisis Tematik Ulasan Google pada Cheesecake Expert Yogyakarta - Reza Restiana (Jurnal Ragam Pengabdian, 2026)
This study aims to understand consumer perceptions of Cheesecake Expert Yogyakarta by utilizing Digital Voice of Customer (Digital VoC) through Google reviews. A descriptive qualitative approach was used with thematic analysis according to Braun and Clarke. A total of 100 reviews were selected based on their relevance to aspects of product quality, price, service, packaging, and consumer trust. The analysis process was assisted by ATLAS.ti 25 through the stages of familiarization, initial coding, theme search, theme review, and theme definition. The results showed five main themes that shape consumer perceptions, namely: product quality, price and value, service and consumer experience, packaging and product practicality, and trust and loyalty. Product quality, especially taste, texture, and appearance emerged as the most dominant factors in shaping satisfaction and influencing repeat orders. Other factors such as affordable prices, friendly service, ease of payment, and halal aspects also strengthened positive consumer experiences. These findings confirm that repeat purchase decisions are influenced by holistic consumer experiences, so that Digital VoC can be a strategic data source for culinary MSMEs in improving service and product quality.